Ectopic choroid plexus papilloma - Khade, Shalaka; Shenoy, Asha (Asian Journal of Neurosurgery, 2018)
Choroid plexus papilloma is a rare intracranial neoplasm. These lesions most commonly present in the fourth ventricle in adults and lateral ventricle in children. Herein, we report a case of a 57-year-old male with complaint of backache of few weeks duration. Magnetic resonance imaging revealed an intradural and extramedullary space occupying lesion at D8 level. Histology showed multiple free-floating papillae with a central fibrovascular core. The cells showed immunoreactivity for vimentin, glial fibrillary acidic protein, synaptophysin, S-100 protein, and cytokeratins (CK, CK7).
Keywords: Choroid plexus papilloma; ectopic neoplasm; extramedullary; intradural